2020
DOI: 10.1002/jso.26055
|View full text |Cite
|
Sign up to set email alerts
|

The impact of metabolic syndrome (MetS) on surgical outcome for patients with mostly HBV‐related hepatocellular carcinoma (HCC) underwent hepatectomy

Abstract: Background and ObjectivesThe impact of metabolic syndrome (MetS) on surgical outcome, mostly in patients with HBV‐related hepatocellular carcinoma (HCC) who underwent hepatectomy.MethodsA propensity score matching analysis was conducted. Patients were categorized into two groups MetS‐related hepatocellular carcinoma (MetS‐HCC) and 1:1 matched non‐MetS‐related HCC (non‐MetS‐HCC). Surgical outcomes were compared between the two groups.ResultsSeventy‐four MetS‐HCC patients and 74 propensity score‐matched non‐MetS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…Previous studies have reported that hepatectomy for patients with MS is safe, feasible and beneficial to prognosis, although the probability of postoperative complications is higher (6,8,10,35,36). Similarly, the incidence of postoperative complications was also high among HBV-infected HCC patients with MS in our cohort, although there was no difference between the two groups (52.1% vs. 49.8%, P= 0.772).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported that hepatectomy for patients with MS is safe, feasible and beneficial to prognosis, although the probability of postoperative complications is higher (6,8,10,35,36). Similarly, the incidence of postoperative complications was also high among HBV-infected HCC patients with MS in our cohort, although there was no difference between the two groups (52.1% vs. 49.8%, P= 0.772).…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic syndrome (MS) is a clinical syndrome of obesity, dyslipidemia (low high-density lipoproteinemia and/or high triglyceridemia), hyperglycemia (diabetes or impaired glucose regulation), and hypertension (4,5). Previous studies have shown that hepatectomy for MS-HCC has a higher but acceptable operative risk, but the long-term survival outcome remains controversial (6)(7)(8)(9)(10)(11). Reasons for the controversy include a small sample size or an uneven baseline of enrolled patients.…”
Section: Introductionmentioning
confidence: 99%
“…Overall complications were assessed based on data from eleven studies [ 17 , 19 , 21 23 , 25 29 , 31 ]. Data on major and minor complications was available in eight [ 17 , 19 , 22 , 25 28 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Specific genetic contributions may help explain differences observed in PAFs for HCC between race/ethnic groups. 29 While insulin resistance likely plays a role in its pathogenesis, oxidative injury and inflammatory reactions could be influenced by genetics. A study performed in the US among Hispanic, NH black and NH white individuals identified the variant, rs73809, (148M) in patatinlike phospholipase domain-containing protein 3 (PNPLA3) as a predictor for hepatic fat content.…”
Section: Discussionmentioning
confidence: 99%